Analysis of endometrial lavage microbiota reveals an increased relative abundance of the plastic-degrading bacteria Bacillus pseudofirmus and Stenotrophomonas rhizophila in women with endometrial cancer/endometrial hyperplasia - Chao, Angel; Chao, An-Shine; Lin, Chiao-Yun; Weng, Cindy Hsuan; Wu, Ren-Chin; Yeh, Yuan-Ming; Huang, Shih-Sin; Lee, Yun-Shien; Lai, Chyong-Huey; Huang, Huei-Jean; Tang, Yun-Hsin; Lin, Yu-Shan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The pathogenic influences of uterine bacteria on endometrial carcinogenesis remain unclear. The aim of this pilot study was to compare the microbiota composition of endometrial lavage samples obtained from women with either endometrial hyperplasia (EH) or endometrial cancer (EC) versus those with benign uterine conditions. We hypothesized that specific microbiota signatures would distinguish between the two groups, possibly leading to the identification of bacterial species associated with endometrial tumorigenesis. A total of 35 endometrial lavage specimens (EH, n = 18; EC, n = 7; metastatic EC, n = 2; benign endometrial lesions, n = 8) were collected from 32 women who had undergone office hysteroscopy. Microbiota composition was determined by sequencing the V3−V4 region of 16S rRNA genes and results were validated by real-time qPCR in 46 patients with EC/EH and 13 control women. Surprisingly, we found that Bacillus pseudofirmus and Stenotrophomonas rhizophila – two plastic-degrading bacterial species – were over-represented in endometrial lavage specimens collected from patients with EC/EH. Using computational analysis, we found that the functional profile of endometrial microbiota in EC/EH was associated with fatty acid and amino acid metabolism. In summary, our hypothesis-generating data indicate that the plastic-degrading bacteria Bacillus pseudofirmus and Stenotrophomonas rhizophila are over-represented within the endometrial lavage microbiota of women with EC/EH living in Taiwan. Whether this may be related to plastic pollution deserves further investigation.